Internal structure of intonational categories: The (dis)appearance of a perceptual magnet effect - Rodd, Joe; Chen, Aoju (Frontiers in Psychology, 2023)
The question of whether intonation events have a categorical mental representation has long been a puzzle in prosodic research, and one that experiments testing production and perception across category boundaries have failed to definitively resolve. The present study takes the alternative approach of looking for evidence of structure within a postulated category by testing for a Perceptual Magnet Effect (PME). Perceived goodness and discriminability of re-synthesised productions of Dutch rising pitch accent (L*H) were evaluated by native speakers of Dutch in three experiments. The variation between these stimuli was quantified using a polynomial-parametric modelling approach. PME was detected: (1) rated “goodness” decreased as acoustic-perceptual distance relative to the prototype increased (Experiment 1), and (2) equally spaced items far from the prototype were more frequently discriminated than equally spaced items in the neighbourhood of the prototype (Experiment 2). These results provide first evidence for internal structure of pitch accents, similar to that found in colour and phoneme categories. However, the discrimination accuracy gathered here was lower than that reported for phonemes. The PME discrimination symptom disappeared when participants were tested on a very large number of stimuli (Experiment 3). These results suggest a more transient nature of the perceptual magnet effect in the perception of pitch accents and arguably weaker categoricality of pitch accents, compared to that of phonemes and in particular of lexical tones.